Modern Radiological Imaging of Osteoarthritis of The Hip Joint With Consideration of Predisposing Conditions - Weber, M.-A.; Merle, C.; Rehnitz, C.; Gotterbarm, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Osteoarthritis is the most common disease of the hip joint in adults and has a high socioeconomic impact. This review article discusses the value of three imaging modalities in the diagnosis of osteoarthritis of the hip joint: projection radiography, computed tomography, and magnetic resonance imaging (MRI). Besides established imaging diagnostics of osteoarthritis, this review also outlines new MRI techniques that enable the biochemical analysis of hip joint cartilage and discusses predisposing deformities of the hip joint including femoroacetabular impingement (FAI) with labral pathologies, hip joint dysplasia, malrotation, and, finally, femoral head necrosis, for which early detection and an exact description of the extent and localization of the necrotic area are extremely important. Conventional X-rays remain indispensable for the diagnosis of osteoarthritis, while MRI is able to depict additional early symptoms and signs of activity of the disease. With the increasing number of joint-preserving interventions such as surgical hip luxation and hip joint arthroscopy for treating FAI, high-resolution imaging is gaining further importance for both pre- and postoperative diagnostics because it can accurately recognize early stages of joint damage. With high-resolution MR sequences and MR arthrography, the detailed depiction of the thin cartilaginous coating of the hip joint has become quite possible.Key points:• Projection radiography is the method of choice for the diagnostic work-up of osteoarthritis of the hip joint.• Using computed tomography, the amount of acetabular bone stock prior to total hip arthroplasty is assessed in selected patients.• Magnetic resonance imaging can substantiate the indication of surgery in case of discrepancy between clinical symptoms and radiological findings of the hip joint.• If distinct and left untreated, predisposing conditions (such as femoroacetabular impingement) may lead to early development of osteoarthritis of the hip joint.• Functional cartilage imaging can verify changes in the biochemical composition of the cartilage before they become morphologically evident.Citation Format:• Weber MA, Merle C, Rehnitz C et al. Modern Radiological Imaging of Osteoarthritis of The Hip Joint With Consideration of Predisposing Conditions. Fortschr Röntgenstr 2016; 188: 635 – 651
Keywords: hip joint; osteoarthritis; magnetic resonance imaging; projection radiography; computed tomography; femoroacetabular impingement